The relationship between physical activity and diet on Body Mass Index of elementary school students - Cahyo Wibowo; RLNK Retno Triandhini; Rizky Setiawan; Yahya eko Nopiyanto (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
Physical activity and diet are factors that affect nutritional status, excessive energy intake and not being balanced by physical activity will certainly increase the risk of having underweight, which is not ideal. This study aimed to determine the relationship between physical activity and diet on the BMI of SDN 2 Polobogo students. The research method is analytic observational with a cross-sectional design. The research population is students of SDN Polobogo 2 Class IV-VI. The sample in this study amounted to 40 students. The instrument in this study used the SQ-FFQ questionnaire, the PAQ-C questionnaire, and the measuring instrument for height and weight. Data analysis technique using pearson correlation test, which continued with multiple linear regression. This study's results indicate a significant effect between physical activity and diet on the BMI of grade 4-6 students at SDN Polobogo 2, Semarang Regency. It can be seen that physical activity and diet together have a positive effect on students' BMI. It can be concluded that physical activity and diet are significantly related to the BMI of students in grades 4-6 SDN Polobogo 2 Semarang Regency